Analisis untuk pengaruhi Innovation dan Management Control Systems sebagai variabel Moderasi terhadap Performance. - Novia Wahyu Duwi Wardani (Universitas Islam Malang, 2017)
AbstackThe purpose of abstrack this is to analyze the influence of innovation, andmanagement control system as avariable moderation against performance researchmethods used is an explanatory that if the same data researchers describing thecausal relationship between variables variable by hypothesis testing data used inthis study is the primary.While the sample used in this study is employees PTLANGGENG MAKMUR INDUSTRI Tbk technique probability sampling.Research this shows that of the firs testwariatel innovation not affect the variableperformance testing to two variable innovation and management control systemaffect significantly againts performance ande variable innovation, can not affectthe performance whil thevariabe management control system affect significantlyto the performance.Keyword:innovation, management control system , performance